Fertilización química en cultivo de maní (Arachis hypogaea), en la parroquia San Antonio, cantón Paltas - Gallegos Lalangui, Freddy Bladimir (2024)
The present research work was carried out on a private farm in the San Antonio parish of the Paltas canton, Loja province, with the aim of determining the most appropriate fertilization dose to increase production in peanut cultivation. (Arachis hypogaea L. var. criollo). For its implementation, a completely randomized block design (CRBD) with a factorial arrangement was used, with three treatments and three replications in 10 experimental units in an area of 250 m². The land preparation and layout of the experimental units of 2.50 x 3.70 were carried out, followed by the selection, disinfection, and treatment of the seeds for planting at a density of 30 x 40 cm. The treatments used were as follows: NPK 35g + Nitrofoska 12-1816 15g + nitrofoska 12-16-18 35g. T2 Urea 35g + Nitrofoska 12-18-16 20g + Potassium muriate 35g. T3 NPK 35g + Nitrofoska 12-18-16 15g + Potassium muriate 35g applied at 22, 42, and 58 days after planting. Cultural practices such as manual weed control were carried out. The evaluated variables were based on the crop's phenology; germination, plant height, presence of inflorescence, number of stems, number of leaves, stem thickness, yield variables; the latter taken after the harvest which was carried out 104 days after sowing, pod length, seed weight obtained from the random selection of 5 plants per experimental unit. For the statistical analysis of data, the InfoStat software was used, employing analysis of variance. (ANOVA). A survey was conducted with a considerable sample of producers near the study area to collect information about their production and to fulfill the second objective, which consists of comparing the 5% increase in production in relation to the producers in the area. The phenological stages did not show statistically significant differences between the treatments regarding the duration time of each stage. However, the treatments did have an impact on production, with treatment T3 NPK 35g + Nitrofoska 12-18-16 15g + Muriate of potash 35g showing the best results, achieving a value of 2967,06 kg/ha. Therefore, the research and analysis of variance indicate the production obtained, while in the other treatments, lower production values were obtained. The application of the interview with producers allowed for the collection of information on the management they perform on peanut cultivation; cultivated area, seed variety, types of fertilization, fertilization dosage, cultural practices, aspects affecting production, and production obtained. The analysis of the producers' information indicates that the production is 1080.00 kg per hectare. Comparing with the production obtained from the present research work in which treatment T3 showed a production of 2967,06 kg/ha, it is concluded that the objective of a 5% increase was achieved.